2002
DOI: 10.1038/sj.mp.4001122
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of temperament as vulnerability factors in depression

Abstract: In order to evaluate the hypothesis that one set of genetic risk factors may be common to disorders and dimensions of temperament, whereas environmental risk factors are disorder specific, we have conducted a genetic analysis of dimensions of temperament and symptoms of depression in about 201 pairs of monozygotic and dizygotic twins. Dimensions of temperament associated with novelty seeking, harm avoidance, reward dependence, and persistence were measured by using the Temperament and Character Instruments dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 24 publications
2
44
0
2
Order By: Relevance
“…Epidemiological research shows that personality affects stress resilience, psychosocial adaptation and risk for mental and physical disease. [1][2][3][4] Considerable interest has therefore been directed at uncovering the biological basis of personality. Cloninger proposed an influential operationalization of personality, a tripartite model based hypothetically on neurotransmitter neurobiology with three basic stimulus-response characteristics: Novelty Seeking, Harm Avoidance and Reward Dependence, measured by the Tridimensional Personality Questionnaire (TPQ) and thought to be related to dopaminergic, serotonergic and noradrenergic neurotransmission, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological research shows that personality affects stress resilience, psychosocial adaptation and risk for mental and physical disease. [1][2][3][4] Considerable interest has therefore been directed at uncovering the biological basis of personality. Cloninger proposed an influential operationalization of personality, a tripartite model based hypothetically on neurotransmitter neurobiology with three basic stimulus-response characteristics: Novelty Seeking, Harm Avoidance and Reward Dependence, measured by the Tridimensional Personality Questionnaire (TPQ) and thought to be related to dopaminergic, serotonergic and noradrenergic neurotransmission, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Schwartz, Snidman, and Kagan (1999) found that 61% of the toddlers who avoided novelty displayed anxiety symptoms in adolescence, whereas only 27% of the toddlers who were uninhibited showed anxiety symptoms in adolescence. There is some indication that fear/shyness shares a common genetic liability with depression and anxiety, which may partially explain the predictive effects (Goldsmith & Lemery, 2000;Ono et al, 2002). In addition, numerous studies have linked parental depression with child internalizing behavior (NICHD Early Child Care Research Network, 1999;Spence, Najman, Bor, O'Callaghan, & Williams, 2002).…”
Section: Internalizing Behaviormentioning
confidence: 99%
“…The unfolding of adolescent internalizing behavior might begin with the child's exposure at birth to a genetic and an environmental liability (i.e., a depressed parent). The genetic liability may translate into a fearful/shy temperament in early childhood, as there is evidence to suggest a genetic connection between early temperamental fearfulness and later anxiety/depression (Goldsmith & Lemery, 2000;Ono et al, 2002). Mediating processes during later childhood and adolescence might enhance the likelihood that early exposure to maternal depression and temperamental fear/ shyness will result in the expression of internalizing problems during adolescence.…”
mentioning
confidence: 99%
“…However, panic disorder and social phobia predict subsequent alcohol problems in adolescents and young adults (Zimmermann et al, 2003). Also, twin studies have demonstrated genetic correlations between HA and internalizing disorders (Ono et al, 2002). Finally, internalizing psychopathology may be a more important predisposing factor in women than men (Dell'Osso et al, 2002;Prescott et al, 1997).…”
Section: Introductionmentioning
confidence: 99%